Zambia - More Jobs and Prosperity in Zambia : What Would it Take? Based on the Jobs and Prosperity : Building Zambia’s Competitiveness Program - World Bank (World Bank, 2012)
While Zambia's economy performs well, in macroeconomic terms, low levels of productivity plague industry, and this constrains growth, diversification and prosperity. In recent years, economic growth has averaged 5-6 percent a year, business reforms are being implemented, and investment levels are at an all time high. However, according to the World Economic Forum's global competitiveness index 2010-2011, Zambia is not a competitive place in which to do business (ranking 115th out of 139 countries). Not surprisingly, business productivity tends to be low, and few Zambian industries are internationally competitive. Formal employment is shrinking and rural poverty is increasing. In summary, there is an urgent need to increase productivity, growth and employment. These questions continue to preoccupy policy makers, businesses and civil society especially in light of government's strategy to embrace private sector-led growth and facilitate competitiveness and diversification. The Jobs and Prosperity: Building Zambia's Competitiveness (JPC) Program is an effort to answer these questions and, at the same time, to achieve some concrete results that improve industry productivity and competitiveness. The Zambian government, with support from donors, has, for a long time, been trying to raise prosperity by encouraging more productive businesses, more competitive and diverse industries, and greater employment. Yet these efforts have not generated the results sought. The goal of the JPC Program is to achieve some meaningful progress towards improving industry productivity and competitiveness. The Program focuses on four industries so as to build traction and keep the scope of work manageable. The industries were selected by a group of Zambian stakeholders. The Program facilitated a process through which Zambian stakeholders identified some narrowly defined target results that, if achieved, could help these industries become more productive and then supports initiatives to achieve these results.